SETTLEMENT OF PROBLEMATIC FINANCING THROUGH RELIGIOUS COURTS (CASE STUDY OF BPRS AL-WASHLIYAH) - Azizan Rizky Ramadhan; Rahmad Efendi (Program Pascasarjana UIN Sumatera Utara, 2025)
Problematic financing is a crucial challenge for the sustainability of Islamic banking, including the Sharia People's Financing Bank (BPRS). At BPRS Al Washliyah, the increasing phenomenon of problem financing has a direct impact on the bank's financial stability and has given rise to disputes between customers and financial institutions. This study aims to examine three main issues: (1) factors causing problem financing at BPRS Al Washliyah, (2) the mechanism for resolving problem financing through the Religious Court, and (3) the role and authority of the Religious Court in resolving problem financing disputes based on Islamic law and positive law in Indonesia. This study uses a juridical-empirical approach, with a legal research method that examines secondary data through literature studies and primary data through interviews and documentation at BPRS Al Washliyah and the Medan Religious Court. The results of the study indicate that problem financing is triggered by weak financing analysis, changes in customer economic conditions, and negligence in carrying out contracts. Dispute resolution through the Religious Court is carried out through a civil lawsuit with the legal basis of Law No. 21 of 2008 and the DSN-MUI Fatwa. Religious Courts play a crucial role in resolving Sharia economic disputes, not only as adjudicative institutions but also as guarantors of Sharia justice principles. This study concludes that the integration of Islamic legal principles and positive law through Religious Courts is an effective instrument in upholding justice and resolving problematic financing disputes in Sharia banking.